Changes in diet and food shopping behaviors among Asian-American adults due to COVID‐19 - Pasquale E. Rummo; Rhea Naik; Lorna E. Thorpe; Stella S. Yi (Wiley, 2021)
Abstract Objective COVID‐19 has changed diet and food shopping behaviors, but a lack of disaggregated data by racial and ethnic subgroup makes it challenging to identify whether specific populations are experiencing greater challenges in safely securing an adequate food supply and engaging in healthy eating behaviors during the pandemic. Thus, the objective of this study was to measure such changes among Asian-American (AA) adults, overall and by ethnic subgroup. Methods Using a nationally derived nonprobability sample, 3084 AA adults were recruited, including 1737 East Asian, 570 South Asian, 587 Southeast Asian, and 124 multiethnic Asian adults. Participants completed an online survey with questions related to sociodemographics, health status, and diet and food shopping behaviors, including questions related to COVID‐19. Logistic and linear regression were used to compare differences in survey responses by Asian ethnic subgroup. Results Compared to other AA subgroups, a higher percentage of Asian Indian (17%), Filipino (13%), Vietnamese (12%), and Korean (11%) adults reported no longer getting food resources they were receiving before COVID‐19 (e.g., mobile meals, food pantry items). The percentage of Filipino (8%) and Vietnamese (7%) adults who reported not having enough money to buy food they need was also higher than other AA subgroups. And a higher percentage of Asian Indian adults (7%) reported not having a way to get to the food store since COVID‐19 than other AA subgroups. Conclusions Previous work has not included disaggregated data, which may mask important disparities in food access and food insecurity among people hit hardest by COVID‐19, such as Filipino, Vietnamese, and Asian Indian households.